PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE PICTURE AND PICTURE UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS III SD NEGERI 37 PEKANBARU - Siti Mayasari; Lazim N. (JURNAL PAJAR (Pendidikan dan Pengajaran), 2019)
The background in this study is the low social studies learning outcomes of third-grade students of SD Negeri 37 Pekanbaru. The purpose of this study is to improve social studies learning outcomes by applying the cooperative learning model type picture and picture. The subjects of this study were class III B SD Negeri 37 Pekanbaru totaling 35 students. The results showed that student learning outcomes experienced an increase in the base score was 57.28 to 70.71, an increase of 23.45%. The average score from base to cycle 2 to 83.42 increased by 45.63%. Based on the research that has been done, it can be concluded that the application of the cooperative and learning model type picture and the picture has been proven to be able to improve the learning outcomes of social studies in Grade III students at SD Negeri 37 Pekanbaru.